마우스 모델에서 풋사과 에탄올 추출물 경구 투여에 따른 대장염 완화 - 장하나(Ha Na Jang); 배의진(Ui-Jin Bae); 장미(Mi Jang); 이성현(Sung Hyen Lee); 김기창(Gi-Chang Kim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2023)
본 연구에서는 풋사과 에탄올 추출물이 대장염으로 인한 체중, 대장 길이의 감소를 효과적으로 억제할 뿐만 아니라 결장 조직의 위축과 세포 내 염증을 감소시켰음을 확인하였다. 또한 대장염과 같은 염증성 질환에서 높은 농도로 존재하는 사이토카인의 생성을 억제하였다. 이와 연관된 항염증 작용기전을 추정하기 위해 NF-κB 신호전달과 관련 단백질 발현을 확인하고 염증반응 신호를 억제하는 것으로 확인되었다. 우리는 이러한 항염증 효과가 플라보노이드 물질과 관련이 깊다는 선행연구에 착안하여 풋사과가 성숙한 사과보다 약 7배의 높은 procyanidin B2 함량이 있음을 확인하였다. 이와 같은 결과는 풋사과가 대장염의 과다 면역반응을 억제하기 위한 기능성 소재로의 활용과 procyanidin B2와 같은 기능 성분의 관련 가능성을 시사한다. 더 나아가 풋사과로부터 분리된 단일물질을 이용한 기능 성분의 명확한 규명과 임상실험과 같은 실증연구를 통해 기능성 식품 소재로의 활용을 기대한다. Procyanidin is known for its antioxidant and anti-inflammatory effects. Using HPLC analysis, we found that the content of procyanidin B2 is nine times higher in unripe apples than in ripe apples. This study, therefore, investigates the anti-inflammatory effects of unripe apple ethanol extraction (UAE) on colitis in mice. The intact intestinal epithelium is the channel for nutrient absorption and is crucial for maintaining good health. We simulated colitis in mice by inducing impairment of the intestinal epithelium-using dextran sodium sulfate. The efficacy of UAE administration for promoting intestinal injury repair in mice was studied in this animal model. We observed that UAE administration inhibited weight loss, pathological damage to the intestinal mucosal layer, and shortening of colon length. Moreover, UAE administration inhibited the increase of inflammatory cytokines in the serum and colon by inhibiting NF-κB signaling. The results that UAE contains high procyanidin and alleviates the symptoms of colitis in mice validate its use as a functional material for improving and treating symptoms of inflammatory bowel disease. KCI Citation Count: 0